Model of Bi-directional Flyback Converter for Hybrid AC/DC Distribution System - Riku Pasonen (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
In this article, a simulation model and concept of two switch bi-directional isolated DC/DC converter is presented. Converter is based on flyback converter type. Also control method for voltage regulation with bi-directional power transfer is presented. Target application of the proposed converter was selected to be a hybrid AC/DC distribution system concept of which was briefly described. The requirement of galvanic isolation in the hybrid AC/DC concept comes from use of shared neutral wire; DC current runs with unbalanced part of AC current in neutral wire. Without galvanic isolation grounded neutral would cause short circuit if DC/DC converter is connected to three phase rectifier or inverter. Simulation was carried out with PSCAD electromagnetic transient simulator.DOI: http://dx.doi.org/10.11591/ijpeds.v3i4.4606